PENGARUH STRUKTUR MODAL, PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PT BUKIT ASAM TBK PERIODE 2012 - 2024 - Rafly Satrio; Faisal Faisal (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of Capital Structure, Profitability, and Liquidity on Firm Value at PT Bukit Asam Tbk for the period 2012-2024. The research method used is a quantitative approach with multiple linear regression analysis using secondary data obtained from the company's annual financial statements, sample stock summary reports, financial position statements and income statements. The independent variables in this study include capital structure (DER), profitability (ROA) and liquidity (CR), while the dependent variable is firm value as measured by Price to Book Value (PBV). The results of the study indicate that partially, DER does not affect firm value with a significance value of 0.520 > 0.05. ROA does not affect firm value with a significance value of 0.248 > 0.05. Meanwhile, CR affects PBV with a significance value of 0.011 < 0.05. Simultaneously, the three independent variables have a significant effect on firm value, with a coefficient of determination (R²) of 0.564. This shows that 41.8% of the variation in company value can be explained by these three variables, while the remaining 58.2% is influenced by other factors.